Classification of Acute Respiratory Distress Syndrome - V. V. Moroz; A. M. Golubev (Общая реаниматология)
The editorial proposes a new classification of acute respiratory distress syndrome (ARDS). Acute lung injury (ALI) is regarded as the first stage of ARDS. Diagnostic tests based on the use of new technologies, such as determination of pulmonary extravascular water, pulmonary capillary permeability index, oxygenation index, and hemodynamic disorders are recommended. The early signs of acute lung injury should be detected to perform early appropriate therapy in order to prevent further complications and to reduce mortality rates.